Development of the Physics Knowledge Enrichment Book “Lightning” to Improve High School Students’ Science Literacy and Environmental Literacy - Febriya, Dhea; Desnita, Desnita; Ratnawulan, Ratnawulan (STKIP Singkawang, 2025)
The independent curriculum emphasizes literacy skills as the most important learning objectives. The two literacies that are greatly needed in the 21st century are science literacy and environmental literacy. However, these two literacies among high school students in Indonesia are still relatively low. The subject that is able to achieve both literacies in an integrated manner is physics. The purpose of this development research is to produce a physics knowledge enrichment book